Konkurenční strategie firmy Rexport, s.r.o. - Hrabálek, Ondřej (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Diplomová práce se zabývá analýzou konkurenčního prostředí na trhu deskových her, na kterém se zvolená firma pohybuje přes sedm let. Dále jsou zhodnoceny stávající procesy a podmínky ve kterých se firma nachází v rámci svých aktivit, mezi které patří internetový prodej, kamenná prodejna a velkoobchod. Firma procházela v průběhu let vývojem, aby udržela krok s konkurencí a nezaostávala za ní. Konkurence bude rozdělena v rámci maloobchodu a velkoobchodu, protože se zde nalézají jiné subjekty a podmínky jsou zcela odlišné. Následně jsou předneseny plány podniku pro následující roky a forma jejich uskutečnění. Návrhy jsou zhodnoceny v rámci konkurenčního prostředí.

This thesis analyzes competitive environment in the market segment of board and card games, where the analyzed company is doing business for more than six years already. First, the study defines and assesses current processes and conditions in each part of corporate activities, including in particular retails sales (both e-shopping and brick and mortar shop), publishing house and wholesale of imported products. Through the recent years, the company has undergone extensive and permanent adaption and transformation in order to retain its competitiveness. Competitors on are different regarding the wholesale and retails segment, given that these markets are separated from each other and business conditions vary significantly. Further, paper will provide actual development plans of company for upcoming years and the methods to reach the proposed goals. Finally, the development business plan and methods are to be evaluated, based on competitiveness criteria.
Competitive Strategy of Rexport Company
Keywords: Deskové hry; karetní hry; analýza konkurence; současný stav; budoucí vývoj; řešení; Board games; card games; future development; solution; competition analysis; current condition